2007
DOI: 10.3168/jds.2007-0257
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis and Lipopolysaccharide from Escherichia coli B:055 Cause Hyperpermeability of Rumen and Colon Tissues

Abstract: The objective of the present investigation was to evaluate the effects of acidic pH of the perfusate and presence of lipopolysaccharide (LPS) on permeability of rumen and colon mucosal tissues to mannitol and LPS using the Ussing chamber system. Rumen and colon tissues (n = 8), obtained from slaughtered feedlot steers, were tested for changes in permeability to (3)H-mannitol under pH of 4.5, 5.5, and 6.5 for rumen and at 5.5, 6.5, and 7.4 for colon, with or without LPS from Escherichia coli B:055 at 500 microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
129
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(140 citation statements)
references
References 17 publications
9
129
1
1
Order By: Relevance
“…In AC1, we also observed a high level of rumen LPS and histamine. Owing to lysis of Gram-negative bacteria under low pH, free LPS concentration can increase in the rumen and its translocation may occur across the rumen epithelium (Emmanuel et al, 2007). Histamine can be produced by Lactobacilli and/or Allisonella histaminiformans that have already been described to survive at low pH in the rumen of cattle (Garner et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In AC1, we also observed a high level of rumen LPS and histamine. Owing to lysis of Gram-negative bacteria under low pH, free LPS concentration can increase in the rumen and its translocation may occur across the rumen epithelium (Emmanuel et al, 2007). Histamine can be produced by Lactobacilli and/or Allisonella histaminiformans that have already been described to survive at low pH in the rumen of cattle (Garner et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that LPS translocates across the rumen wall at a greater rate than across the colon wall, and this translocation was pH independent. On the other hand, it was observed that at acidic pH values of the perfusate there was an increase in the permeability of more than 5-to 6-fold through colon and rumen tissues, respectively, to large molecules such as 3 H-mannitol (Emmanuel et al, 2007).…”
Section: Sources and Translocation Of Endotoxin In Dairy Cowsmentioning
confidence: 99%
“…The main source of endotoxin entrance into the bloodstream before parturition might be the gastrointestinal tract. Previous research demonstrated that DCs have a 3.3-fold greater prevalence of pathogenic E. coli strains in their colon than the healthy ones (Byrne et al, 2003), which indicates that colonic endotoxin might translocate into bloodstream in DC around parturition (Emmanuel et al, 2007). Other potential sources of endotoxin in the periparturient cow are the infected mammary gland (Wenz et al, 2001) and the uterine tissue (Dohmen et al, 2000).…”
Section: Downer Cow Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Ametaj et al (2005) found a strong relationship between blood indicators of inflammation (acute phase proteins, TNFα) and hepatic lipid accumulation in dairy cows. Emmanuel et al (2007 and demonstrated that increasing amounts of barley grain increased concentrations of endotoxin in rumen fluid, and at low rumen pH the transfer of endotoxin across the rumen epithelium was increased. Intermittent administration of endotoxin triggered metabolic and inflammatory responses typically associated with displaced abomasum and retained placenta (Zebeli et al, 2011).…”
Section: Nutritional Management To Control Neb and Optimize Fertilitymentioning
confidence: 99%